The state of Singapore’s civil-military relations : the normalisation of the SAF in Singapore’s society - Sim, Shannon Wen Jie (2019)
This essay is an attempt to reinvigorate the stagnated military history of Singapore. For too long, the military history of Singapore had been taken for granted which is ironic as the military in Singapore has a pervasive presence within the larger society. This is evident from the annual military parades conducted during National Day, National Service which institutionalise universal conscription in Singapore, and the use of advertisements by the SAF which gave a representation of how the military activities are seemingly similar to civilian lives. This normalisation of the military within Singapore’s society would be the subject of examination in this essay which would be achieved through the analysis of the state of Singapore’s civil-military relation over three decades. Through public diplomacy, the evolution of the Singapore Armed Forces (SAF) will be closely studied, alongside with the policies that the SAF had carried out under civilian leadership. The goal of this essay would thus be to study how this normalisation process had taken place over three decades since the 1980s to the 2000s, in which the result would identify symptoms and signals where the spheres of civilian and military activities began merging symbiotically with one another.